Algeria : Growth Prospects in Algeria. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper for Algeria analyzes the growth prospects of the Algerian economy. Drawing on the findings of the empirical growth literature, the paper combines growth accounting and cross-country growth regressions to examine the role of macroeconomic and institutional factors in driving economic growth. It reviews the past growth performance in Algeria and explores the reasons underpinning the recent pickup in nonhydrocarbon GDP growth. The paper also analyzes labor market developments and assesses the factors that may hinder employment creation in Algeria.